2011
DOI: 10.5005/jp-journals-10002-1058
|View full text |Cite
|
Sign up to set email alerts
|

Thyroglossal Duct Carcinoma: A Case Series and Approach to Management

Abstract: Thyroglossal duct carcinoma (TGDC) is a rare disease with few reported series. No clear consensus exists regarding further management after adequate excision of the cyst, especially the role of total thyroidectomy and postoperative radioiodine therapy. We review our experience of nine cases and the literature to clarify the management of this rare condition. A retrospective study over a period of 10 years was performed using the clinical records from Christian Medical College, Vellore to identify patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…They recommended a total thyroidectomy with neck dissection only if lymph node metastases were found on ultrasound or during surgery; followed by radioiodine therapy (14). Some investigators have recommended that a total thyroidectomy must be performed in all patients with TGDC carcinoma, as it could decrease the risk of disease recurrence in future (15,16). In our experience, the benefit of performing a total thyroidectomy in addition to the Sistrunk procedure, in the absence of a suspicious thyroid lesion is questionable.…”
Section: Managementmentioning
confidence: 93%
“…They recommended a total thyroidectomy with neck dissection only if lymph node metastases were found on ultrasound or during surgery; followed by radioiodine therapy (14). Some investigators have recommended that a total thyroidectomy must be performed in all patients with TGDC carcinoma, as it could decrease the risk of disease recurrence in future (15,16). In our experience, the benefit of performing a total thyroidectomy in addition to the Sistrunk procedure, in the absence of a suspicious thyroid lesion is questionable.…”
Section: Managementmentioning
confidence: 93%
“…Few studies in which the patient belongs to low risk group showed no recurrence after Sistrunk procedure [15]. Most literatures advocate minimum of total thyroidectomy as treatment of choice in view of possible multifocality of the tumour as well as clear surgical margin from Sistrunk procedure alone [13,15,16]. When nodal metastases are detected preoperatively, total thyroidectomy and regional neck dissection are recommended in addition to Sistrunk procedure.…”
Section: Incidental Carcinoma On Thyroglossal Cystmentioning
confidence: 99%